1992
DOI: 10.1007/bf01385051
|View full text |Cite
|
Sign up to set email alerts
|

Employee voice to supervisors

Abstract: This article reports the results of two studies examining some factors that increase the likelihood that employees will voice to their supervisors. The way employees perceive that their supervisors manage employee voice was identified as a major cause of the likelihood that employees will voice upward. The Supervisor as Voice Manager Scale is presented along with data demonstrating its reliability and validity. Theoretical and applied implications of the results are discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
133
0
7

Year Published

1999
1999
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 151 publications
(141 citation statements)
references
References 21 publications
1
133
0
7
Order By: Relevance
“…In particular, the existing literature suggests that employees voice more when managers encourage them to provide suggestions, display openness to their ideas, and signal that their input matters and will be considered (see Morrison, 2011Morrison, , 2014. For example, an early study on voice suggested that employees are more likely to express their ideas or concerns when they perceive their managers to be approachable and responsive to voice (Saunders, Sheppard, Knight, & Roth, 1992). Across both qualitative and quantitative studies with cardiac operating surgery teams, Edmondson (2003) showed that coaching behaviour of team leaders facilitates voice of team members.…”
Section: The Role Of Managers' Behaviorsmentioning
confidence: 99%
“…In particular, the existing literature suggests that employees voice more when managers encourage them to provide suggestions, display openness to their ideas, and signal that their input matters and will be considered (see Morrison, 2011Morrison, , 2014. For example, an early study on voice suggested that employees are more likely to express their ideas or concerns when they perceive their managers to be approachable and responsive to voice (Saunders, Sheppard, Knight, & Roth, 1992). Across both qualitative and quantitative studies with cardiac operating surgery teams, Edmondson (2003) showed that coaching behaviour of team leaders facilitates voice of team members.…”
Section: The Role Of Managers' Behaviorsmentioning
confidence: 99%
“…Levinson (7) noted that employees tend to view the organization as a living entity because it has responsibility for the actions of its agents; therefore, they develop global beliefs concerning the extent to which their organization values their contributions and cares about their safety and well-being. Studies have shown that management openness is positively associated with general worker voice (8,9). Clarke (10) showed that workers' intentions not to report safety incidents were related to their perception that management would take no notice.…”
Section: Implications For Publicmentioning
confidence: 99%
“…Employee voices regarding creative and novel ideas are likely to be the identification of the problems in organizations and suggestions for organizational changes that refine predominant routines (Janssen et al, 1998). The employees need to communicate mainly with their supervisors to suggest their ideas (Saunders et al, 1992). Thus, leaders can facilitate employees' innovative behaviors that may encourage or discourage employees from providing novel ideas that may sometimes threaten the status quo (Zhou & George, 2003).…”
Section: Literature Review On Creativity Studiesmentioning
confidence: 99%
“…Subordinates need to consider the readiness of their supervisors before they voice their creative ideas (Janssen, Vries & Cozijnsen, 1998;Whitney & Cooper, 1989;Saunder, Sheppart, Knight & Roth, 1992). The readiness of supervisors is especially critical in the context of idea implementation, in that creative ideas often challenge conventionally accepted organizational patterns and routines (Janssen et al, 2004) and subordinates' voice relates mainly to communication toward superiors (Saunders et al, 1992). In this context, management of emotions may also be important, as emotions show reactions to creative ideas.…”
Section: Introductionmentioning
confidence: 99%